Influence of Pseudomonas fluorescens as Biofertilizer in Secondary Hardening of Tissue Cultured Banana Var. Poovan - Ramesh, Y.; Ramassamy, V. (International Journal of Applied Sciences and Biotechnology, 2015)
The present study brings out the effects of Pseudomonas fluorescens in secondary hardening of tissue cultured banana var.Poovan. Two concentrations (1% & 2%) of liquid medium grown Pseudomonas fluorescens (3×109 cells/ml) were used in borewell water and the growth performance of the banana plantlets was assessed. Seven different growth parameters were studiedviz. shoot weight, height and girth, leaf length, leaf width, no. of leaves and chlorophyll content. Best results were obtained in1%Pseudomonas fluorescens (T2) treatment with average of 10.79gm for weight, 10.25cm for height, 5.3 for no. of leaves, 1.3mmfor girth, 14.96cm for leaf length and 36.6 spad units of chlorophyll content per plantlet compared to treatment (T3) with 2%liquid Pseudomonas fluorescens. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11878 Int J Appl Sci Biotechnol, Vol. 3(1): 38-41